1975
DOI: 10.1002/bip.1975.360141214
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of glutaraldehyde with poly(α,L‐lysine), n‐butylamine, and collagen. I. The primary proton release in aqueous medium

Abstract: SynopsisThe interaction between poly(a,L-lysine) (G = 180) and glutaraldehyde was investigated in dilute aqueous solution by measurement of the kinetics of proton release a t constant pH and temperature and a t various concentrations of the reaction components. Under various conditions, the release of protons a t constant pH appeared kinetically to be composed of a t least two steps: an initial zero-order reaction, followed by a slower reaction.At excess of polylysine amino groups, the pH optimum for the rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Short exposure of the crystals to higher or lower pHvalues had only small effects on the slow base uptake which presumably originated from some byproducts of the reaction of glutaraldehyde with the protein. Similar effects were noted by BLAUER et al (4) from the interaction between glutaraldehyde and collagen.…”
Section: Autodigestionsupporting
confidence: 87%
“…Short exposure of the crystals to higher or lower pHvalues had only small effects on the slow base uptake which presumably originated from some byproducts of the reaction of glutaraldehyde with the protein. Similar effects were noted by BLAUER et al (4) from the interaction between glutaraldehyde and collagen.…”
Section: Autodigestionsupporting
confidence: 87%
“…Some confidence in this assumption can be obtained from similar observations for the radical polymerizations of vinyl stearate monolayers,13 polycondensation of glycine cetyl ester monolayers,13 and saponification of stearate monolayers by Ca2+. 25 Further, studies of the primary proton release in aqueous solution reactions between 1,5-pentanedial(glutaraldehyde) and PL showed that the pH optimum for the reaction rate was at pH [9][10]26 the range in which ? ?srel also attains its maximum value.…”
Section: Resultsmentioning
confidence: 99%